(untitled) (Global Journal of Science Frontier Research, 2020)
The call for sustainability in all spheres of life is more noticeable in the construction industry. To avoid this, the study examines the professional perception of factors militating against building services maintenance among tertiary institutions in Lagos megacity of Nigeria, with a view of providing pertinent information to the policies makers and general public. To achieve this, two hundred and fifty (250) questionnaires were systematically administered among built environment professionals across the institution in the study area. The result of the findings revealed that among the factors militating against building service maintenance within the study area, non-development of potential risks and contingency plan, inadequate storage facilities and altitude of workers, and underutilization and non-utilization of available resources were the highest militating factors against building services maintenance in the study. Based on this, the study recommends the needs for adequate provision of storage space for workers, and sustainable utilization of available resources in a way that will yield maximum output.